Tiada Lagi Hukuman Kekal: Universalisme Kristosentris Karl Barth sebagai Jaminan Keselamatan di Akhir Sejarah Manusia - Kiding Allo, Christian Arisandi (Asosiasi Teolog Indonesia, 2024)
This article explores the concept of eternal punishment in light of the Christocentric universalism Karl Barth outlines in his seminal work Church Dogmatics. While Barth explicitly rejects the doctrine of apokatastasis, his treatment of election and reconciliation suggests that salvation is already accomplished for humanity, rendering eternal damnation unnecessary. Using a literature review methodology, this study examines key themes in Church Dogmatics II and IV, including Christ’s election and the interplay between grace and sin. The findings highlight Barth’s assertion that eternal punishment is not possible. However ineffective sin might prove to be, Barth by no means diminishes its seriousness. Instead, he emphasizes the work of Christ as central to the doctrine of salvation.